Multiparty, relation with patology of pregnancy and delivery - L. Andrejevic; A. Andrejevic; V. Nestorovic; B. Milosevic; S. Andrejevic; S. Nestorovic (IMR Press, 2020)
Introduction: Multiparty is a long-standing problem for gynecologists around the world, since in places where multiparity is expressed, researchers are not able to fully examine it, most often because of socio-economic reasons. Objective: The aim of this research was to examine the influence of multiparty (delivery of six or more children ) on pathology of pregnancy and delivery. Materials and Methods: The study included women that were delivered at the Gynecological Clinic of Faculty of Medicine in Pristina during 1992 and 1993, a total of 12, 532. The analysis included impact of multiparity on pathology of pregnancy and delivery. Results: The analysis of the age of patients indicates that the highest number of patients was aged between 18 and 25 years. As an atypical phenomenon, the authors also presented a pelvic presentation, although it cannot be considered a pathological condition, but is listed here because it can give an increased number of birth complications. The percentage of cesarean section in multiparas is growing but not evenly. Multiparity certainly increases its incidence. The abruption of normally inserted placenta is more frequent in multiparas. Placenta previa is also more common in multiparas. Situs transversus indicates an increased number of internal turnings as well as cesarean section. Edema, proteinuria, hypertension (EPH) gestosis at multiparas regularly determines the end of pregnancy with cesarean section. Episiotomy is rare in multiparas. Rh incompatibility is not more frequent at multiparas. Multiparity is also correlated with pathological conditions associated with umbilical cord swelling. Multiparas experience more common bleeding during the third and fourth trimesters. Rupture of amnion is more common in multiparas. Hysterectomy after delivery is significantly dependent on parity. Conclusion: The limit for multiparty was set to delivery of six or more children. Multiparity certainly has an adverse effect on pregnancy. The pathology of pregnancy as well as complications during delivery were increased. Multiparity ultimately poses danger to the pregnant woman.